Genealogy of Time and Space in Schelling’s Die Weltalter - Augusto, Roberto (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The aim of this article is to analyze the concepts of time and space in Schelling’s Die Weltalter. We will study the three versions of this text. In the 1811 version, we will see how Schelling defends a concept of organic time opposite to mechanical time. The Trinity composed by the Father (past), Son (present) and Spirit (future) will allow him to develop his «system of times». In the 1813 and 1815 versions, we will deal intensively with the points not treated by Schelling in 1811.